Long-run impacts of the conflict in Ukraine on food security in Africa - Lacina Balma; Tobias Heidland; Sebastian Jävervall; Hendrik Mahlkow; Adamon N. Mukasa; Andinet Woldemichael (Kiel Institute for the World Economy (IfW Kiel), 2022)
Many African countries heavily rely on imports of agricultural commodities and agricultural inputs from Ukraine and Russia, for example wheat, other grains, and fertilizer. Russia's invasion of Ukraine has disrupted global access to grains due to reduced production, exports, and increased trade costs. This policy brief investigates the possible long-term consequences of the conflict on food security in Africa. We use a long-run general equilibrium trade model and study three scenarios that may evolve as a consequence of the conflict: 1) Ending exports of Ukrainian wheat and other cereals for food production, such as corn or sorghum. 2) Russia's potential ban on exports of grains and fertilizers, and 3) The impact of increased trade costs due to disrupted trade routes in the Black Sea. The model simulations show the conflict will severely compromise food security in Africa. We document important cross-country heterogeneity in the severity of impacts. – – Viele afrikanische Länder sind stark von Importen von Agrargütern und Inputs aus der Ukraine und Russland abhängig, beispielsweise Weizen, anderen Getreiden und Dünger. Russlands Invasion der Ukraine gefährdet die weltweite Verfügbarkeit von Getreide aufgrund reduzierter Produktion, geringeren Exporten, und gestiegenen Handelskosten. Dieser Policy Brief untersucht die möglichen langfristigen Auswirkungen des Konflikts auf die Ernährungssicherheit in Afrika. Wir verwenden ein langfristiges allgemeines Gleichgewichtsmodell, um drei Szenarien, die in Folge des Konflikts entstehen könnten, zu analysieren. 1) Ein Ende der Exporte ukrainischen Weizens und anderer Getreide für die Lebensmittelproduktion, beispielsweise Mais und Hirse, 2) Ein möglicher Stopp russischer Getreide- und Düngerexporte, und 3) Der Einfluss gestiegener Handelskosten aufgrund der gestörten Handelsrouten im Schwarzen Meer. Die Modellsimulationen zeigen, dass der Konflikt die Ernährungssicherheit in Afrika gefährdet. Wir dokumentieren wichtige Länderunterschiede in der Schwere der Betroffenheit.
Keywords: 330; Food security; Grains; Fertilizers; Africa; Ukraine conflict; General equilibrium trade model; Ernährungssicherheit; Getreide; Dünger; Afrika; Ukraine-Konflikt; Allgemeines Gleichgewichtsmodell